Soluble Starch Synthase Enzymes in Cereals: An Updated Review - Ahsan Irshad; Huijun Guo; Shoaib Ur Rehman; Xueqing Wang; Chaojie Wang; Ali Raza; Chunyun Zhou; Yuting Li; Luxiang Liu (Agronomy, 2021)
Cereal crops have starch in their endosperm, which has provided calories to humans and livestock since the dawn of civilization to the present day. Starch is one of the important biological factors which is contributing to the yield of cereal crops. Starch is synthesized by different enzymes, but starch structure and amount are mainly determined by the activities of starch synthase enzymes (SS) with the involvement of starch branching enzymes (SBEs) and debranching enzymes (DBEs). Six classes of SSs are found in Arabidopsis and are designated as soluble SSI-V, and non-soluble granule bound starch synthase (GBSS). Soluble SSs are important for starch yield considering their role in starch biosynthesis in cereal crops, and the activities of these enzymes determine the structure of starch and the physical properties of starch granules. One of the unique characteristics of starch structure is elongated glucan chains within amylopectin, which is by SSs through interactions with other starch biosynthetic enzymes (SBEs and DBEs). Additionally, soluble SSs also have conserved domains with phosphorylation sites that may be involved in regulating starch metabolism and formation of heteromeric SS complexes. This review presents an overview of soluble SSs in cereal crops and includes their functional and structural characteristics in relation to starch synthesis.